Tinjauan Yuridis Prompt Release Procedure Dalam Menangani Tindak Pidana Perikanan Di Zona Ekonomi Eksklusif Indonesia - Haridus, Haridus; Sudardi, Sudardi; Buntoro, Kresno (UI Scholars Hub, 2023)
Article 292 UNCLOS is a novel provision, both in the law of the sea and in general international law, as no such provision existed before the Convention was adopted. The purpose of procedure is to reconcile the interests of the detaining State in its measures against the flag State. Generally, the flag State wishes its vessel and its crew released promptly while the interest of the detaining State to secure the court appearance of the Master and the payment of penalties. Under Indonesian law, the procedure regarding prompt release is regulated in the provisions of Article 104 of Law Number 45 of 2009. The earlier study stated Article 292 UNCLOS empowers ITLOS to order the release of vessels, which have been detained by a coastal State for violations committed by the vessels in the its EEZ which have not been set free upon the posting of a reasonable bond. This article highlights how international and national law that regulate and implement these procedures.